Obesity, Diabetes and Atrial Fibrillation; Epidemiology, Mechanisms and Interventions - Asghar, O.; Alam, U.; A. Hayat, S.; Aghamohammadzadeh, R.; M. Heagerty, A.; A. Malik, R. (Current Cardiology Reviews, 2012)
The last few decades have witnessed a global rise in adult obesity of epidemic proportions. The potential impact of this is emphasized when one considers that body mass index (BMI) is a powerful predictor of death, type 2 diabetes (T2DM) and cardiovascular (CV) morbidity and mortality [1, 2]. Similarly we have witnessed a parallel rise in the incidence of atrial fibrillation (AF), the commonest sustained cardiac arrhythmia, which is also a significant cause of cardiovascular morbidity and mortality. Part of this increase is attributable to advances in the treatment of coronary heart disease (CHD) and heart failure (HF) improving life expectancy and consequently the prevalence of AF. However, epidemiological studies have demonstrated an independent association between obesity and AF, possibly reflecting common pathophysiology and risk factors for both conditions. Indeed, weight gain and obesity are associated with structural and functional changes of the cardiovascular system including left atrial and ventricular remodeling, haemodynamic alterations, autonomic dysfunction, and diastolic dysfunction. Moreover, diabetic cardiomyopathy is characterized by an adverse structural and functional cardiac phenotype which may predispose to the development of AF [3]. In this review, we discuss the pathophysiological and mechanistic relationships between obesity, diabetes and AF, and the challenges posed in the management of this high-risk group of individuals.
Keywords: morbidity